2011
DOI: 10.1038/onc.2010.590
|View full text |Cite
|
Sign up to set email alerts
|

The fungicide ciclopirox inhibits lymphatic endothelial cell tube formation by suppressing VEGFR-3-mediated ERK signaling pathway

Abstract: Ciclopirox olamine (CPX), an off-patent antifungal agent used to treat mycoses of skin and nails, has recently been demonstrated to be a potential anticancer agent. However, the underlying mechanism is not well understood. Here for the first time we show that CPX inhibited lymphangiogenesis in an in vitro model (tube formation). This effect was in part associated with inhibition of vascular endothelial growth factor receptor 3 (VEGFR-3) expression, as overexpression of VEGFR-3 conferred partial resistance to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…The ability of LECs transfected with miR-9 mimics or inhibitors to form capillary networks was evaluated by endothelial tube formation assay in the absence or presence of TNF-␣ (20 ng/ml) as described elsewhere with some modifications (38). After 96-well plates were precoated with 40 l of Matrigel per well, they were allowed to polymerize for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of LECs transfected with miR-9 mimics or inhibitors to form capillary networks was evaluated by endothelial tube formation assay in the absence or presence of TNF-␣ (20 ng/ml) as described elsewhere with some modifications (38). After 96-well plates were precoated with 40 l of Matrigel per well, they were allowed to polymerize for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, CPX has been shown to inhibit the proliferation of cells in culture (1012) and of breast cancer and myeloma xenograft growth in mice (11–13). CPX also inhibits angiogenesis and lymphangiogenesis in established culture models (10, 14). DEF inhibits the growth of HeLa cells derived from cervical carcinoma as well as other cancer cell lines (15), and its analog mimosine slows the growth of subcutaneous lung and pancreatic cancer xenografts in mice (16).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, preclinical studies have found that this off-patent fungicide possess anticancer effect, by inhibiting cell proliferation, inducing cell death, as well as inhibiting angiogenesis and lymphangiogenesis [5, 710, 12]. Most recently, a phase I clinical trial has demonstrated that oral administration of CPX at a dose of 40 mg/m 2 once daily for 5 days is well tolerated in all patients, and induces disease stabilization and/or hematologic improvement in 2/3 patients with advanced hematologic malignancies [6].…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly support that systemic administration of CPX has a great potential to be repositioned for cancer therapy. To facilitate repurposing CPX for cancer therapy, many groups have investigated the molecular mechanisms underlying its anticancer action [5, 710, 12]. Of interest, a recent study has reported that CPX enhances parthenolide-induced cell death in acute myeloid leukemia cells, by inhibiting the phosphorylation of S6K1 (T389), implying inhibition of mTORC1 [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation